PENGARUH KUALITAS PELAYANAN, LOKASI DAN HARGA DALAM MENENTUKAN KEPUASAN KONSUMEN DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING PADA RUMAH MAKAN BIRU DAUN KABUPATEN SITUBONDO - Zuhdi, Farhan Tri Nanda; Pramitasari, Triska Dewi; Praja, Yudha (Fakultas Ekonomi dan Bisnis, 2025)
In an ever-evolving and competitive business world, companies must adapt by changing their approach to serving customers, facing competitors, and launching products. This study aims to determine the influence of Service Quality, Location, and Price on Consumer Satisfaction, with Purchase Intention as an Intervening Variable at Biru Daun Restaurant in Situbondo Regency. The sampling technique used in this study was simple random sampling, with 96 consumers as respondents. Data analysis and hypothesis testing used Partial Least Squares-Structural Equation Modeling (PLS-SEM). The hypothesis test results using the Smart PLS 3.0 application show that service quality positively and significantly affects purchase intention. Location has a positive but insignificant effect on purchase intention. Price has a positive and significant effect on purchase intention. Service quality has a positive but insignificant effect on customer satisfaction. Location has a positive but insignificant effect on customer satisfaction. Price has a positive and significant effect on customer satisfaction. Purchase intention has a positive and significant effect on customer satisfaction. Product quality has a positive but insignificant effect on customer satisfaction through purchase intention. Location has a positive but insignificant effect on customer satisfaction through purchase intention. Price has a positive and significant effect on customer satisfaction through purchase intention.